Description of a new subspecies of the crayfish Parastacus brasiliensis (Von Martens, 1869) from Sao Francisco de Paula, RS, Brazil (Decapoda, Parastacidae) - Fontoura, Nelson Ferreira; Conter, Maria-Rotraut (Zootaxa, 2008)
Parastacus brasiliensis promatensis subsp. n. is described from São Francisco de Paula, Rio Grande do Sul, Brazil. The animals were collected at an elevation of 850 m, representing the first record of Parastacidae at high altitude in Brazil. Subspecies recognition was performed through the analysis of morphometrical characters. Discriminant analysis was applied to compare P. brasiliensis promatensis subsp. n. with the known populations of P. brasiliensis (Von Martens, 1869) using residuals from 23 morphometric regressions (Canonical Correlation = 0.948). All variance was explained by function 1 (Pbrasiliensis promatensis centroid equal to 3.04; P. brasiliensis centroid equal to -2.78).